COMPARATIVE ANALYSES OF SERI HAMLET BEACH SAND, WAILIHA HAMLET MOUNTAIN SAND, AND PASSO VILLAGE RIVER SAND TO THE MORTAR COMPRESSIVE STRENGTH - loppies, putrilia orpha (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2023)
Mortar is part of building construction whose constituent materials consist of a mixture of Portland cement, fine aggregate (sand), and water. Sand serves as an important material in the manufacture of mortar. According to the place of collection, sand is classified into beach sand, mountain sand, and river sand. This study focuses on the comparison of the compressive strength of mortar using beach sand in Seri hamlet before and after washing, mountain sand in Wailela hamlet, and river sand in Passo village. The test objects in this study were 96 pieces in cube shape with a size of 5 × 5 × 5 cm for a study time of 7 and 28 days. The highest compressive strength occurred in the mortar of the Seri hamlet beach sand after washing by 24.37 MPa, followed by the mortar of the Seri hamlet beach sand before washing by 20.34 MPa. The mountain sand mortar in Wailela hamlet got 16.12 MPa, and the lowest compressive strength existed in the river sand mortar in Passo village at 12.27 MPa.